CHANGE OF ORGANIZATIONAL CULTURE - GAJDA, Joanna (Trends in education, 2013)
The company, that does not comply with its role, based on the principles of conduct will have to resolve a cultural development. In response to the culture crisis requires strengthening of functional elements of the existing culture, and designing but also implementation of a new culture,accordingly adjusted. It is a chance to re-establish the organization in its development cycle. The purpose of this paper is to present the organization of the process of cultural change.
Keywords: organizational culture; the crisis of culture; the diagnosis of culture; a culture change